Literatura de monteiro lobato no ensino de ciências - Groto, Silvia Regina (2012)
Advocating education as a humanizing task, the humanizing function of literature and the importance of scientific education, this paper proposes linking Science and Literature in Science Teaching using two specific books of Monteiro Lobato in the final series of elementary school level. Adopting the action research methodology, an interdisciplinary approach, we used the books A Reforma da Natureza and Serões de Dona Benta in two classes (8th and 9th) at Escola Estadual Professor José Mamede, located in the town of Tibau do Sul, Rio Grande do Norte. The readings were performed in Portuguese Language s course and the scientific content were discussed in Science´s classrooms. The book A Reforma da Natureza permitted to approach issues related to the environment, while the use of Serões de Dona Benta showed particularly its effectiveness in questioning the concepts of matter, mass, weight and some questions about the Nature of Science (NOS). In general, the analysis of results shows that the readings of these two books permitted interaction and dialogicity in the classroom, as well as indicates the potential of these books in contextualing and questioning the scientific content contained in it. We advise, however, the need for the science teacher be aware of the conceptual mistakes present in literary works, avoiding erroneous learning and reinforcement of alternative conceptions